Newgrange og den hvide mur - Eriksen, Palle (Kuml, 2004)
Newgrange and the white wall Newgrange, 50 km north of Dublin, receives 200,000 visitors annually and is probably the most famous and most visited passage grave in the world (Figs. 1-2). It was constructed around 3400 BC. The fact that the huge mound contained a passage grave was not revealed until 1699. In 1870, a deep ditch was dug all the way around the mound in order to let the kerbstones and their ornamentation be seen more clearly, and a stone wall was built on top of the border stones to prevent the earth of the mound from sliding into the ditch (Fig. 3). In the course of time, the mound was increasingly worn down, and some of the large stones in the chamber and passage became unstable. This was a major problem because of the many visitors. Representatives of the Irish state, which had acquired Newgrange, therefore decided to have the mound renovated, and a committee was established for this purpose. This committee in turn asked Professor Michael J O’Kelly to head an investigation and restoration of the monument. Between 1962 and 1975 O’Kelly and his team spent four years of fieldwork investigating Newgrange. The committee had specified one of the tasks as being to restore the natural sloping surface of the mound. However, the project turned out differently. Once O’Kelly had investigated the structure of the mound and observed, at several points, the layer sequence in the mound-filling that had subsided, he came up with the provocative idea that Newgrange had looked completely different from the common conception of its structure. In 1982, Michael O’Kelly published his investigations and described the context of the restoration in the book “Newgrange. Archaeology, Art and Legend”. The layer sequence of the mound just east of the entrance can be seen in the profile illustrated in Fig. 4. The mound filling mainly consists of loose stones, divided by layers of turf. O’Kelly thought that all the mound’s layers were contemporary. Outside the kerbstone numbered K95 both the subsided earth and a culture layer deposited by a Beaker-settlement around 2300 BC are visible. A “quartz/granite layer” with large amounts of small white quartz pieces was found in a wide belt outside the kerbstones. Outside the kerbstones this layer could be followed across a 105-metre long stretch (i.e. 43% of the mound’s circumference) in a width of 6-7 metres. According to O’Kelly, this layer had originally covered the front of a 3-metre tall retaining wall on top of the kerbstones on both sides of the entrance. However, the wall had been unable to withstand the pressure from the mound and had eventually given way and tipped over. Consequently, Newgrange had had a totally different appearance during the Stone Age: “Stone walls are necessary where the mound is built of loose stones, but a turf wall would be quite adequate and completely effective where the mound is built of turves or soil. It may be, therefore, that the majority of passage-grave mounds had an original drum-like appearance and were not at all the gently sloping rounded mounds which we see in varying states of collapse to-day. Newgrange was such until excavation revealed that it had the revetment wall which has now been restored.” Consequently, O’Kelly had a concrete wall built, which was covered by the quartz (Fig. 5). The passage and the chamber were embedded in concrete. The entrance of the passage grave was completely altered in order to facilitate access for the many visitors. This area of the wall was covered with dark stones (Fig. 6) to underline the fact that this was not the original appearance. Newgrange had again become an impressive monument, and many visitors find it spectacular (Fig. 1). And spectacular it is – almost too spectacular! In 1982, John Michell commented on the newly restored Newgrange: “New Grange [has been] transformed in recent years into an archaeological show-site after undergoing drastic excavations … Only a few years ago New Grange was scientifically dug into, many of its interior and other stones were disturbed, and the reconstructed model, now curiously faced with a layer of ornamental pebble-dash of quartz and boulders to represent someone’s theory of how it originally looked, lets in rain through the roof for the first time in history.” Others have observed that as there was no concrete in the Stone Age, the wall could not have been as vertical as it is now. The Loughcrew-field with its more than 30 passage graves was discovered and investigated during the 1860s by Eugene A. Conwell. Here it suffices to take note of the description of the two largest and best-preserved mounds, Mound L and Mound T, as these two mounds are important for understanding the original layout of Newgrange. “L is forty-five yards in diameter, surrounded by 42 large stones, laid lengthwise on their edges, and varying from six to twelve feet in length, and from four to five feet high. Great quantities of the loose stones which formed the apex of this carn have been removed, of which there are very visible evidences.” (Fig. 7). On Mound T – to which he has given the much more interesting name of “the Tomb of Ollamh Fodhla” after a legendary Irish king – Eugene Conwell writes: “The original shape of this carn still remains comparatively perfect, consisting of a conical mound of loose stones … It is thirty-eight and one-half yards in diameter at the base, having an elevation of twenty-one paces in slant-height from base to summit. A retaining wall, consisting of thirty-seven large flags [kerbstones] laid on edge, and varying in length from six to twelve feet, surrounds the base externally … Inside the retaining wall of large flag stones, as far as was examined, and, apparently, going all round the base of the carn, was piled up a layer, rising from three to four feet in height, and about two feet in thickness, of broken lumps of sparkling native Irish quartz …” (Fig. 8). At Loughcrew T, Eugene Conwell noticed that the white quartz had been arranged like a collar a little up the hillside, just inside the row of kerbstones. Apparently, this was a common feature of many of the mounds at Loughcrew, because the ridge with the many mounds is also called Carnbane, which is Irish for “the white mounds.” When I saw Loughcrew L and T in 1999, I realised that this could have been what Newgrange used to look like. Newgrange had changed a lot in the course of time; it had to contain several phases, just like the Irish passage graves of Baltinglass Hill and Newgrange site K (Fig. 9). Knowth is situated less than 2 kilometres from Newgrange. In a number of ways, the two Neolithic barrows are identical. Professor George Eogan carried out the investigation of Knowth, which began in 1962, the same year that Michael O’Kelly started investigating Newgrange. In Knowth, there are two passage grave chambers, one with a passage towards the west, the other with a passage towards the east. Outside and on either side of the passages’ entrances in front of the chain of kerbstones are large areas sprinkled with what Eogan calls “exotic stones”, such as white quartz. Eogan suggests that these layers may have something to do with the site of the mound: “However, excavation has not produced enough evidence wholly to confirm this theory, and we cannot rule out the likelihood that this spread, or at least its lower part, was a deliberately laid feature.” In addition, he continues: “The spread of exotic stones may also have played a role in the suggested ceremonies. They could have embellished the edge of the mound as a background for the ceremonies … After the ceremonies the stones might have been spread, a ‘cloth’ to protect and emphasize the ceremonial, possibly altar, area; it may be noted that the exotic stones occur on the old ground surface.” Similarly, some Danish dolmens and passage graves have areas of white stones along the mound side and in front of the entrances. In these cases, the stones are white-burnt flint and not quartz. Such a layer was found at the passage grave of Kong Svends Høj (King Svend’s Mound), and it has been interpreted as a sacrificial layer. The white-burnt flint may also have been arranged as a collar a little up the hillside, just as Conwell interpreted the quartz arrangement at Loughcrew T. O’Kelly thought that the quartz had been arranged in a three-metre tall wall on top of the kerbstones at Newgrange. Today, it is difficult to interpret the profile in Fig. 4 in this way, because that would imply that the wall had been pressed outwards all at once in its whole length, like a gate falling forward so that it is stretched flat on the ground with its entire height. If the wall really existed, it would more likely have collapsed gradually, and the fallen granite and quartz would have piled up in a heap just in front of the kerbstones. The quartz and granite would not have ended so far from the edge as they in fact did. The appearance of Dowth, the third Neolithic barrow by the Bend of Boyne, also contradicts O’Kelly’s collapse theory. Although Dowth is taller and so has a steeper hillside than Newgrange and Knowth, its kerbstones were not hidden by fallen stones. Usually, burial mounds consist of two or more phases, and the mounds are extended successively. The Neolithic mounds may also have several phases. It is less well known that dolmens and passage graves may also have more phases. In Denmark it is possible, in broad outline, to distinguish five steps (Fig. 10). If we take another look at the Newgrange profile, we are able to identify several possible phases (Fig. 11). If at the same time we take into consideration that the turf layers may not have been laid by humans but may instead be natural vegetation layers, this would support the idea of a gradual change in Newgrange’s appearance during the prehistoric era. Here, just as in nature, the vegetation side of the turf layers is turned upwards and not downwards, whereas the vegetation side would usually be turned downwards in turf-built mounds. Phase 1: The foot of the mound is marked by a small stone wall, situated 6.5 metres from the present kerbstones. If the kerbstones were present, phase 1 would belong to step C. However, it is more likely that the mound had no kerbstones at this early stage. Just 12 kilometres from Newgrange is the passage grave of Fourknocks I, which was investigated in 1950. It had no kerbstones, but the foot of the mound was marked by a low stone wall (Fig. 12). Moreover, it is possible that Newgrange had an even older phase, because the passage has a peculiar bend half way along its length, which may indicate the original foot of the mound. Phase 2: The distance between the foot of the mound and the kerbstones is reduced to just under 2.5 metres. Step C. Between the mound and the kerbstones was an open area, perhaps a forecourt, which may have been used for cult ceremonies and processions. Such an open area would explain why many of the kerbstones also are ornamented on the inside. Phase 3: If the complete stone layer between turf layers T2-3 and T3-4 is interpreted as one single phase, the kerbstones would have been hidden, and we would be dealing with a step E mound. More likely there are two phases in this layer, so that the surface of phase 3a was in line with the top of the kerbstones, corresponding to a step D mound – the classical passage grave mound such as Loughcrew T and perhaps Knowth. If in fact there were a phase 3a, phase 3b would belong to a step E mound. Phase 4: This phase also belongs to a step E mound. However, the layer may also have been created by material that had slid down from the upper part of the mound. When the mound was enlarged from phase 1 to phase 3a, the passage may have been lengthened by adding the outer three pairs of passage orthostats. This is indicated by the fact that these three stones are taller than the neighbouring stones in the passage, as opposed to the usual case in passage graves, where the heights of the orthostats in the passage decrease towards the outside (Fig. 13). These three pairs of stones also differ in having an unusually large distance between the third and fourth supporting stones on the northern side of the passage – exactly where a possible earlier termination of the passage would have been. The present exit of the light channel in the side of the mound above the entrance was constructed when the passage was extended. The light channel already existed – it was just extended. Passages in other Irish passage graves have been extended – for instance, at Newgrange Site K (Fig. 9), which is situated a mere 100 metres from Newgrange. Whether this theory of several phases at Newgrange is correct could be confirmed or rejected by new C-14 datings. At first it would suffice to have the top layers analysed. They are rather easily accessible. One of the turf layers was previously dated to 300 AD. Around the mound of Newgrange, twelve large stones are situated at a distance of 7 to 17 metres from the mound’s kerbstones (Fig. 1). These stones can be inscribed in a large circle surrounding the mound. O’Kelly thought that such a stone circle would originally have consisted of 35-38 stones at a distance from each other of 7-9 metres. However, it is much more likely that the preserved stones towards the southeast indicate the Stone Age appearance of the large circle. Thus, there may have been 19 stones surrounding the mound (Fig. 14). The non-typical location of stone 2 also has to be taken into consideration. Michael O’Kelly knew that his restoration of Newgrange was not popular with everyone. He used to speak ironically of his opponents by saying that they wished themselves back to the romantic days when cattle were grazing on the mound, and the passage and chamber were lit by candles (Fig. 15). However, his radical and faulty restoration of Newgrange quite needlessly continued the tradition of the early 20th century, when it was popular for restorers to tear down medieval churches and castles and rebuild them largely according to their own taste. At the beginning of his book on Newgrange, Michael O’Kelly quoted one of his predecessors, E.P. Wright, who in 1900 had said: “To be a restorer of ancient monuments one should be sheltered by a triple coat of brass, but even a repairer of such required a coat of mail.” May this small comment on Newgrange help to punch a hole in Michael O’Kelly’s armour and in the hideous white wall of Newgrange! Palle Eriksen Ringkøbing Museum Translated by Annette Lerche Trolle